Economic autonomy as a determinant of physical activity behavior in Chinese older adults - Liu, Yuanheng; Luo, Xianglin; Xu, Hao (Frontiers in Public Health, 2025)
BackgroundThe physical activity of the old people is affected by many factors, and the economic situation is an important factor affecting the physical activity. However, the relationship between economic autonomy and physical activity patterns among older adult Chinese has not been fully studied.ObjectiveTo investigate the association between different types of economic autonomy and physical activity patterns among Chinese older adults aged 60 and above.MethodsCross-sectional analysis of 1,961 participants from the 2018 China Health and Retirement Longitudinal Study (CHARLS). Economic autonomy was categorized into autonomous and non-autonomous groups. Physical activity was assessed through type, frequency, duration, and purpose, using validated questionnaires.ResultsEconomic autonomy showed positive associations with low and moderate-intensity physical activities (p < 0.05). However, economically non-autonomous individuals demonstrated higher participation in high-intensity physical activities, primarily due to work-related demands (78.7%). The frequency of physical activity was significantly different among economic autonomy groups (p < 0.01).